Welded joints geometry testing by means of automated structured light scanning - Filippov, German; Sednev, Dmitry; Salchak, Yana (Eastern-European Journal of Enterprise Technologies, 2018)
Nuclear industry in Russia plays an important role in total power generation. At the same time, it is considered to be dangerous in terms of high potential risk in a case of any failure occurrence. Therefore, constant monitoring and quality control is essential on every stage of energy production process, as well as maintenance of the technical quality of the exploited components. For that reason, specified regulatory documents are developed. They provide quality requirements for each component type and regulate inspection procedures. In this paper, welded joints were considered as the controlled object. It is represented that standard quality control methods based on the manual visual inspection are not accurate enough. Therefore, this paper suggests an advanced method of automated optical scanning for misalignment evaluation of welded parts based on structural light technique. Precision improvement was achieved by implementation of a robotic manipulator, which led to the development of the specific calibration technique. Considering that there are no established methodologies for such method the validation experiments were performed. The ability to detect the minimum displacement in accordance with nuclear industry regulatory documents was studied. The results demonstrated that misalignment of 0.47 mm can be measured, and it proves that proposed method can be further implemented for a practical application in nuclear industry